MODULUS ELASTISITAS DAN MODULUS PECAH PAPAN PARTIKEL SEKAM PADI - Arbintarso, Ellyawan Setyo; Wibowo, Hary (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Rice husk particle board was expected to replace the established one, because it has advantages such as more heat and fire resistance that can be used in household appliances, building material, heat absorber, and cold storage. As an alternative building material, rice husk particle board should pass the testing processes that suitable to industrial standard include physical and mechanical properties. Particle board was made of resin and rice husk at 1:2 and 1:3 composition mixture and compacted ratio at 2:1, 3:1, 4:1 and 5:1 respectively used moulding that have a measurement 20 x 10 cm2. The testing included internal bonding, modulus of elasticity (MOE), modulus of rupture (MOR) and density of particle board. The results have shown that composition mixture 1:2 has more strength than 1:3. The highest compacted ratio needed more compacted pressure, i.e. on compacted ratio 5:1 has needed pressure 10.795 kg/cm2. Internal bonding of composition mixture of 1:2 has higher than 1:3. The highest value of MOE and MOR have received in 1:2 composition mixture with 5:1 compacted pressure are 5,088.75 kg/cm2 and 63.75 kg/cm2 respectively. The MOE on composition mixture of 1:2 has higher than 1:3. A particle board density ranges from 0.355 g/cm3 on 1:2 composition mixtures with 2:1 compacted pressure to 8.73 g/cm3 with 5:1 compacted pressure. The best of rice husk particle board used 1:2 composition mixture and compacted pressure of 5:1 which result in highest of MOE and MOR values.